PUBLIC SERVICE LOGIC: A SYSTEMATIC LITERATURE REVIEW AND FUTURE RESEARCH AGENDA - Pratama, S.IAN., MPA, Muhammad Rizki; Ni Putu Febi Wulandari; Anisa Maharani (Universitas Kadiri, 2024)
Public Service Logic (PSL) has emerged as a prominent topic in contemporary discussions on the fundamentals of public service delivery, challenging the mainstream principles dominated by New Public Management (NPM). Essentially, PSL is grounded in a service-dominant approach, while NPM follows a product-dominant approach. This distinction implies that public services should focus on co-creating value rather than relying solely on one-sided product delivery. This study aims to systematically analyze the literature on PSL through a systematic literature review method. The review is crucial for understanding the dynamics and trajectory of PSL research, as well as identifying existing research gaps to inform future research agendas.